Anatomo-clinical and Etiological Profile of Nephropathies Biopsied in the Nephrology Department of the Thies Regional Hospital (Senegal) - Dieng, Ameth; Ndongo, Modou; Fall, Rokhaya; Diawara, Mame Selly; Cissé, Mouhamadou Moustapha (Journal of Clinical Nephrology, 2024)
Introduction: In many developing countries, particularly in Africa, the use of renal biopsy (RB) in clinical nephrology is severely lacking. The objectives were to describe the anatomoclinical and etiological profile of these biopsied nephropathies, as well as the factors associated with the etiology of the nephropathies. Patients and method: This was a retrospective descriptive and analytical study from 1 April 2020 to 30 October 2022. The patients were selected from the renal biopsy register of the nephrology department of the Thiès Regional Hospital. Sociodemographic, clinical, biological, and histological parameters were studied. Results: 75 renal biopsies were included. The mean age was 33.3 ± 14.8 years, with a male predominance (65.3%). The main indications were nephrotic syndrome in 50.67% of cases. RB was adequate in 82.7%, inadequate in 13.3%, and borderline in 4%. Glomerular nephropathies predominated, with focal segmental glomerulosclerosis (FSGS) in 34.7%, membranous nephropathy (MN) in 17.3%, minimal change disease (MCD) in 10.67%, extracapillary glomerulonephritis (ECGN) in 5.3% and lupus nephritis (LN) in 3.9%. Thrombotic microangiopathy (TMA) was found in 9.3%. Chronic tubulointerstitial nephropathy (CTIN) accounted for 5.3% of all RB and acute tubular necrosis (ATN) for 4%. The etiologies were primary in 48%, secondary in 28%, and undetermined in 24%. In the bivariate analysis, the etiology was correlated with the mean SBP (p = 0.023), the mean level of hemoglobin (p = 0.028), the levels of GFR (p = 0.017), and the type of kidney disease (p = 0.000). Conclusion: Glomerular nephropathy was more frequent and FSGS was the most common histological lesion found. Primary causes predominated. Associated factors were identified to improve patient management.